4. \( \begin{aligned} 3 x+2 y & =12 \\ 2 x-4 y & =0\end{aligned} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
The Deep Dive
To solve this system of equations, we can use the substitution or elimination method. Let's use the elimination method here. First, align both equations: 1. \( 3x + 2y = 12 \) (Equation 1) 2. \( 2x - 4y = 0 \) (Equation 2) To eliminate \(y\), we can multiply Equation 1 by 2 and Equation 2 by 1: - \( 2(3x + 2y) = 2(12) \) → \( 6x + 4y = 24 \) (Equation 3) - \( 1(2x - 4y) = 1(0) \) → \( 2x - 4y = 0 \) (Equation 2 remains unchanged) Now, add Equation 3 and Equation 2: \[ (6x + 4y) + (2x - 4y) = 24 + 0 \] \[ 6x + 2x + 4y - 4y = 24 \] \[ 8x = 24 \] \[ x = 3 \] Now substitute \(x = 3\) back into Equation 1 to find \(y\): \[ 3(3) + 2y = 12 \] \[ 9 + 2y = 12 \] \[ 2y = 3 \] \[ y = \frac{3}{2} \] The solution to the system of equations is \(x = 3\) and \(y = \frac{3}{2}\).